Rediscovery of Chiretolpis erubescens (Hampson, 1891) (lepidoptera: Erebidae: Arctiinae), A Rare Moth Species in Nilgiris, Tamil Nadu, India - Samson, Arockianathan; Moinudheen, N.; Abinesh, Anbazhagan; Mahesh, R.; Ali, N. Sadiq (Journal of the Bombay Natural History Society (JBNHS), 2024)
No Abstract.